1998
DOI: 10.1098/rsta.1998.0288
|View full text |Cite
|
Sign up to set email alerts
|

Porosity waves in a fluidized sand–column test

Abstract: Fluidized sand-column experiments performed at the IKU provided insight into the mechanism of density adjustment to the conditions of flow against the direction of gravity, and for hydraulic gradients around and past the critical value corresponding to the 'quick' condition. X-ray computer-tomography scan images obtained during these tests show a process which could be described as a kinematic density or porosity-wave motion. Forchheimer's flow law, holding in the post-critical regime, is calibrated by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This reactive‐infiltration mechanism (see review in De Wit ()) was used to explain patterns observed in a variety of geological processes including oil recovery (Daccord et al, ), karst formation (Ortoleva et al, ; Szymczak, ), fluid ascent in the crust (Koulakov et al, ), melt migration (Jordan & Hesse, ; Hewitt, ; Hesse et al, ; Liang et al, ; Keller & Katz, ; Rudge et al, ; Schiemenz et al, ; Weatherley & Katz, ; Spiegelman et al, ), and inner core growth (Sumita et al, ). It also led to numerous studies aiming at reproducing instabilities in the laboratory (Osselin et al, ; Pec et al, ; Vardoulakis et al, ) and developing the theoretical framework to model this process (Szymczak & Ladd, , ; Wangen, ).…”
Section: Introductionmentioning
confidence: 99%
“…This reactive‐infiltration mechanism (see review in De Wit ()) was used to explain patterns observed in a variety of geological processes including oil recovery (Daccord et al, ), karst formation (Ortoleva et al, ; Szymczak, ), fluid ascent in the crust (Koulakov et al, ), melt migration (Jordan & Hesse, ; Hewitt, ; Hesse et al, ; Liang et al, ; Keller & Katz, ; Rudge et al, ; Schiemenz et al, ; Weatherley & Katz, ; Spiegelman et al, ), and inner core growth (Sumita et al, ). It also led to numerous studies aiming at reproducing instabilities in the laboratory (Osselin et al, ; Pec et al, ; Vardoulakis et al, ) and developing the theoretical framework to model this process (Szymczak & Ladd, , ; Wangen, ).…”
Section: Introductionmentioning
confidence: 99%